Soil physico-chemical properties and microbial diversity on chilli anthracnose disease severity in Northern Karnataka, India - Simran Panigatti; Devarajan Thangadurai; Jeyabalan Sangeetha; Ravichandra Hospet; Govardhana Guggalada Yadav; Smita Shinde; Vijaykumar Narayanaswamy Kondenahalli; Prabhudeva Shantappa Ajjappalavara; Poojashree Nagappa Kummur; Umesh Madar; Jiaojiao Song; Kasem Soytong (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Chilli anthracnose disease causes a huge commercial loss in the globe. Studying soil physico-chemical properties is crucial to understand chilli anthracnose because these properties significantly affect the efficacy of biocontrol agents and herbicides used to manage the disease. This study aimed to evaluate the relative percentage of disease incidence (% DI) of chilli anthracnose in dominant chilli growing areas of Northern Karnataka in India and its relationship to soil properties. The soil physico-chemical (texture, moisture, density, pH, EC, OC, N, P, K, Ca, Mg, S, Zn, Cu, Fe, and B) properties, microbial (fungi and bacteria) diversity of 17 soil samples were analysed by standard protocols and evaluated their correlation with % DI, using Pearson correlation and cluster analysis method. Highest % DI was found in Shira with more value of pH (8.45), and Mg (14.63 meq 100 g-1), whereas in Nela with more value of EC (0.38%), moisture (46%), and Ca (33.83 meq 100 g-1), and also in the regions where the beneficial microbes were less in number (Tegg, Shira, Agad and Nela). The results obtained from Pearson correlation indicated that % DI was positively correlated to moisture (r=0.851**, P=0.01), EC (r=0.488*, P=0.05) and negatively correlated to Pseudomonas sp. (r=-0.322*, P=0.05). The present study provides comprehensive information about the role of physical, chemical and biological properties of soil characteristics responsible for the development of anthracnose disease prevalence and reducing soil quality as well as chilli production under natural conditions.